Unusual drainage of the main kidney on accessory kidney - Erdem, Gülnur (Turk J Urol, 2014)
Patients with an accessory kidney are characterized by an excessive number of kidneys. The ureter of the accessory kidney either drains separately into the bladder or merges with the ureter of the main kidney. In our case, interestingly, the ureter of the left main kidney drained directly into the accessory kidney and the ureter of the latter was the common drainage route for both. The drainage of a normal kidney via the ureter of an accessory kidney has not been reported in the literature, so far. The aim of this report is to present the case with radiological findings and to emphasize the effects of this situation on planned surgical procedures. A 62-year-old female patient had an interesting abnormality on the left collecting system, which was revealed on excretory urography (EU), retrograde urography (RU) and multidetector computed tomography (MDCT). A kinky left ureter, which formed a U shape, was revealed on EU. On MDCT, an accessory kidney was revealed at the anterior aspect of the middle zone of left main kidney. The ureter of the main left kidney drained directly into the accessory kidney. The course of this drainage was confirmed by retrograde urography. An accessory kidney is a rare entity associated with horseshoe kidney, ectopic ureter draining into the vagina, bifid collecting system and coarctation of the aorta. In our case, an unusual association between the ureters of the main and accessory kidneys was revealed, which may have an impact on planned surgery in the groin and retroperitoneal areas.